Evaluating the impacts and benefits of sheldgeese on crop yields in the Pampas region of Argentina: a contribution for mitigating the conflicts with agriculture - Gorosabel, Antonella (2019)
Conflicts between waterfowl and agriculture are common in many nations around the world. However, these birds can also provide a variety of benefits that humanity can obtain from nature. There are three migratory and endemic sheldgeese (Ruddy-headed Goose Chloephaga rubidiceps, Ashy-headed Goose Chloephaga poliocephala and Upland Goose Chloephaga picta) which are species of conservation concern in Argentina. Sheldgeese are in constant conflict with the agricultural practices in the Pampas region of Argentina. The objective was to measure possible damages and benefits due to geese grazing on winter wheat crops during different growth stages, in the southeast of Buenos Aires province, Argentina. We established a stratified random plot design in nine fields, where we placed geese exclosure plots and plots without exclosure, allowing sheldgeese to graze. From May to September, we visited each field every two weeks. We performed transects where we counted and collected feces in order to estimate the grazing intensity. We analyzed the total concentration of Nitrogen (N) and Phosphorus (P) in the feces in the period before and after the wheat emergence. We also performed microhistogical analysis to evaluate sheldgeese diet in these two periods. During the crop growth and at harvest, we evaluated possible damages (wheat cover, percentage of eaten plants, percentage of eaten tillers, chlorophyll content, grain yield per plot, harvest index, weight of 1000 grains) and benefits (number of tillers per plant, percentage of weed cover, protein content) of geese grazing. We found that sheldgeese grazing varied along the different visits and among the experimental fields. Geese grazing negatively affected the wheat cover but there was no effect on the final yield. The input of nutrients provided by sheldgeese feces was higher in the period after the crop emergence, when they only ate wheat. Results on the birds’ diet showed that they fed on weeds before wheat emergence thus providing an ecosystem service. In this study, we found elements that could help to shed light on the real impact of sheldgeese in crops and discovered some benefits that these birds could be providing to crops in the Pampas ecoregion.